β-Arrestin2 mediates the initiation and progression of myeloid leukemia - Fereshteh, Mark (National Academy of Sciences, 2012)
β-Arrestins were initially discovered as negative regulators of G protein-coupled receptor signaling. Although β-arrestins have more recently been implicated as scaffold proteins that interact with various mitogenic and developmental signals, the genetic role of β-arrestins in driving oncogenesis is not known. Here we have investigated the role of β-arrestin in hematologic malignancies and have found that although both β-arrestin1 and -2 are expressed in the hematopoietic system, loss of β-arrestin2 preferentially leads to a severe impairment in the establishment and propagation of the chronic and blast crisis phases of chronic myelogenous leukemia (CML). These defects are linked to a reduced frequency, as well as defective self-renewal capacity of the cancer stem-cell population, in mouse models and in human CML patient samples. At a molecular level, the loss of β-arrestin2 leads to a significant inhibition of β-catenin stabilization, and ectopic activation of Wnt signaling reverses the defects observed in the β-arrestin2 mutant cells. These data cumulatively show that β-arrestin2 is essential for CML disease propagation and indicate that β-arrestins and the Wnt/β-catenin pathway lie in a signaling hierarchy in the context of CML cancer stem cell maintenance.